(untitled) (Research, Society and Development, 2022)
The healing of cutaneous wounds is a challenge in clinical surgery, requiring new therapeutic methods for the process to be optimized and performed adequately. In this aspect, photobiomodulation with low intensity laser light (LLLT) has been studied and applied as an adjuvant treatment in this process. Studies have evaluated that lasers can be used satisfactorily, optimizing the repair process of these wounds. The objective of this integrative review was to review the use of photobiomodulation with led light and laser in the process of wound healing. As a search strategy, a bibliographic search was made in electronic databases: PubMed, Lilacs and Web of Science, and selected studies performed in humans and in vivo laboratory with rats, between the years 2010 and 2021. A combination of the following keywords was used: LED light, laser, in vivo, human and laboratory. Fifty-two studies were selected, of these, forty were eliminated as duplicates and fourteen were included for the purpose of qualitative analysis. In all the studied articles, the laser therapy obtained positive results, acting satisfactorily to the objectives. After the analysis of the studies, it can be concluded that photobiomodulation with low intensity laser and LED have shown to be effective, satisfactorily improving the entire process of tissue repair. However, there is a need for more knowledge and studies for the therapy to be really incorporated into clinical practice.